2018
DOI: 10.1038/s41398-018-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and cross-sectional investigations of long-term potentiation-like cortical plasticity in bipolar disorder type II and healthy individuals

Abstract: Visual evoked potential (VEP) plasticity is a promising assay for noninvasive examination of long-term potentiation (LTP)-like synaptic processes in the cerebral cortex. We conducted longitudinal and cross-sectional investigations of VEP plasticity in controls and individuals with bipolar disorder (BD) type II. VEP plasticity was assessed at baseline, as described previously (Elvsåshagen et al. Biol Psychiatry 2012), and 2.2 years later, at follow-up. The longitudinal sample with VEP data from both time points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 83 publications
4
30
1
Order By: Relevance
“…A total of 38 healthy participants (20 females, 18 males; age 24.2 ± 2.0 years, age range 21-31 years) were included in the analysis to be on par with studies demonstrating clear effects on VEP plasticity 5,12 . Seven additional participants were not included in the analysis: two participants suffered from a febrile infection that might have influenced VEP amplitudes, one participant was identified as being amblyopic after screening, and four participants did not complete the protocol due to technical issues.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 38 healthy participants (20 females, 18 males; age 24.2 ± 2.0 years, age range 21-31 years) were included in the analysis to be on par with studies demonstrating clear effects on VEP plasticity 5,12 . Seven additional participants were not included in the analysis: two participants suffered from a febrile infection that might have influenced VEP amplitudes, one participant was identified as being amblyopic after screening, and four participants did not complete the protocol due to technical issues.…”
Section: Subjectsmentioning
confidence: 99%
“…VEP plasticity has since been established as a tool to examine patterns of disturbed neural plasticity in mental disorders. Decreased VEP plasticity in the visual cortex has been described in patients suffering from schizophrenia 8,11 , depression 5 , and bipolar disorder 7,12 . In these conditions, noninvasive brain stimulation in distinct cortical areas is increasingly applied as a biological treatment approach, potentially acting by normalizing neural plasticity 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Using various sensory stimulation paradigms, several studies have documented impaired LTP-like plasticity in schizophrenia ( 45 , 48 ), as well as in individuals at clinical high risk for developing a psychotic disorder (Jacob et al, under review) and in bipolar II disorder ( 49 51 ) and major depressive disorder ( 52 ). Previously, we showed that visual high frequency stimulation (VHFS; ~8.9 Hz) induced sustained (enduring for at least 22 min post-VHFS) potentiation of visual N1b and C1 VEP amplitudes in healthy individuals but not in patients with schizophrenia ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous genome-wide DNA methylation analysis, KIT Ligand ( KITLG ) (cg27512205) methylation was positively associated with childhood trauma and served as a mediator between childhood trauma and blunted cortisol stress reactivity in healthy controls (8). Since impaired cortisol stress reactivity is associated with bipolar disorder (9, 10), this could imply an association between KITLG methylation with bipolar disorder. Moreover, bipolar disorder patients also report higher levels of childhood adversity (11), which may lead to higher KITLG methylation if the previous findings in healthy controls were to be extrapolated to bipolar disorder patients.…”
Section: Introductionmentioning
confidence: 99%